Maternal diabetes on fetal endocrine pancreas development in rats - ISABELA L. IESSI; BRUNA DALLAQUA; YURI K. SINZATO; FRANCIANE Q. GALLEGO; JENS H. NIELSEN; GUSTAVO T. VOLPATO; JOSÉ E. CORRENTE; DÉBORA C. DAMASCENO (Anais da Academia Brasileira de Ciências)
Abstract To evaluate if an unfavorable maternal environment induced by hyperglycemia, hypoxia, and oxidative stress status impairs the morphological development of pancreatic islets in the fetuses on days 18 and 21 of pregnancy. Wistar rats were injected with streptozotocin for diabetes induction. At adulthood (3 months), all animals underwent an oral glucose tolerance test (OGTT) for glucose assessment as an inclusion criterion. Following, the animals were mated. On day 18 and 21 of pregnancy, the mothers were killed for blood biochemical data and, fetal pancreas was collected for immunohistochemical analysis. On the GD18/21, the diabetic (D) dams showed higher glycemia, erythropoietin and TBARS levels, and a disorganized cell distribution in fetal pancreatic islets compared to control (C) rat mothers. The fetal endocrine pancreas of D dams presented a higher ratio of insulin-stained cells on GD18. No difference in the immunostaining for PDX-1 was observed. Fetuses of D dams showed a lower ratio of cells immunostained for Ki-67 in GD18 and greater cell proliferation in GD21. At the GD21, the D group showed a higher ratio of cells undergoing apoptosis. Maternal hyperglycemia impairs fetal pancreatic islet structure, which causes functional changes contributing to fetal hyperglycemia at birth